1
Exact Differentials and Integrating Factors
J. R. Rice, AM 105b, 6 February 2008
Consider a first order ode which is given in the form
dy
dx
=
±
M
(
x
,
y
)
N
(
x
,
y
)
.
To solve such an ode is equivalent, after multiplying by
dx
, and rearranging, to finding functions
y
=
y
(
x
)
satisfying
the differential form
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
=
0
As a special case. Let us suppose that the form
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
is a
perfect
differential
(sometimes called an
exact
differential).
That means that a function
f
(
x
,
y
)
exists so that
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
=
df
(
x
,
y
)
,
where
df
(
x
,
y
)
=
±
f
(
x
,
y
)
±
x
dx
+
±
f
(
x
,
y
)
±
y
dy
.
Thus, if such an
f
(
x
,
y
)
does exists, which means that
Mdx
+
Ndy
=
df
for arbitrary ratios of
dx
to
dy,
then it must be the case that
M
(
x
,
y
)
=
±
f
(
x
,
y
)
±
x
and
N
(
x
,
y
)
=
±
f
(
x
,
y
)
±
y
, implying that
±
M
(
x
,
y
)
±
y
=
±
2
f
(
x
,
y
)
±
y
±
x
=
±
2
f
(
x
,
y
)
±
x
±
y
=
±
N
(
x
,
y
)
±
x
To turn that around, if
M
and
N
satisfy
±
M
(
x
,
y
)
±
y
=
±
N
(
x
,
y
)
±
x
, then it can be shown (please
show it) that the differential form
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
is perfect, i.e., that a function
f
(
x
,
y
)
exists (and is unique to within an additive constant) such that
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
=
df
(
x
,
y
)
.
In such case it is trivial to solve
dy
dx
=
±
M
(
x
,
y
)
N
(
x
,
y
)
, and the solutions are just
f
(
x
,
y
)
=
C
(an
arbitrarily chosen constant). If we want the specific solution satisfying
y
=
b
when
x
=
a
, we just
choose the constant
C
=
f
(
a
,
b
)
.
Of course, in general if we are given two functions
M
(
x
,
y
) and
N
(
x
,
y
)
, it must be
anticipated that
±
M
(
x
,
y
)
±
y
²
±
N
(
x
,
y
)
±
x
, and hence that
M
(
x
,
y
)
dx
+
N
(
x
,
y
)
dy
is
not
a
perfect
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document2
differential. Thus the above approach fails.
But let us be optimists and ask as follows: Noting
that the original ode could have equivalently been written as
dy
dx
=
±
²
(
x
,
y
)
M
(
x
,
y
)
(
x
,
y
)
N
(
x
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '08
 Rice
 Thermodynamics, Factors, Derivative, Trigraph, Mdx, Exact differential

Click to edit the document details